2022
DOI: 10.1093/ofid/ofac069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infection Versus Colonization on Clostridioides difficile Environmental Contamination in Hospitalized Patients With Diarrhea

Abstract: Introduction Patients with Clostridioides difficile infections (CDI) contaminate the healthcare environment; however, the relative contribution of contamination by colonized individuals is unknown. Current guidelines do not recommend the use of contact precautions for asymptomatic C. difficile carriers. We evaluated C. difficile environmental contamination in rooms housing adult inpatients with diarrhea based on C. difficile status. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This suggests other potential sources of disease development in the hospital environment. Indeed, while asymptomatic carriers of C. difficile have not been a significant focus of infection prevention efforts, studies have shown that these carriers do shed toxigenic C. difficile spores to their surroundings, which could cause disease ( 14 ). Though carriers have not been consistently identified as major transmitters of C. difficile that causes CDI, recent work has suggested that patients carrying C. difficile asymptomatically may be at elevated risk for the development of CDI ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests other potential sources of disease development in the hospital environment. Indeed, while asymptomatic carriers of C. difficile have not been a significant focus of infection prevention efforts, studies have shown that these carriers do shed toxigenic C. difficile spores to their surroundings, which could cause disease ( 14 ). Though carriers have not been consistently identified as major transmitters of C. difficile that causes CDI, recent work has suggested that patients carrying C. difficile asymptomatically may be at elevated risk for the development of CDI ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests other potential sources of disease development in the hospital environment. Indeed, while asymptomatic carriers of C. difficile have not been a significant focus of infection prevention efforts, studies have shown these carriers do shed toxigenic C. difficile spores to their surroundings that could cause disease 14 . Though carriers have not been consistently identified as major transmitters of C. difficile that causes CDI, recent work has suggested that patients carrying C. difficile asymptomatically may be at elevated risk for development of CDI 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests other potential sources of pathogen exposure in the hospital environment. While asymptomatic carriers of C. difficile have not been a significant focus of infection prevention efforts, studies have shown these carriers do shed viable, toxigenic C. difficile to their surroundings that could cause disease 14 . Several studies have shown evidence of a reduction in CDI cases if asymptomatic carriers are put on similar contact precautions to CDI patients [15][16][17] , but this has not been consistently found 18 .…”
Section: Introductionmentioning
confidence: 99%